Španski pogled na roman Alamut v dobi globalizacije - Francé, Maja (Primerjalna književnost, 2011)
Towards the end of the twentieth century, Alamut began entering into a multicultural dialogue with various European countries. Due to the general threat posed by the Islamic terrorist movement, it experienced political foregrounding, ultimately in Spain, where a deeper level of the Romanesque literary subject was descended to. It turned out that Alamut - as a symbol of a universal negation of violent regimes and also as a metaphor for endangered Slovenian identity and thus the bearer of the Slovenian message - firmly accelerated the Slovenian-Spanish cultural-communication process.
Keywords: Bartol, Vladimir, 1903-1967; Slovene literature; slovenska književnost; literarna recepcija; Spain; Španija; prevodi v španščino; medkulturna komunikacija; terorizem; Bartol, Vladimir: Alamut